Erythropoietin-Stimulating Agent Hyporesponsiveness in Patients Living with Chronic Kidney Disease - Henry H.L. Wu; Rajkumar Chinnadurai (Karger Publishers, 2022)
Background: Erythropoietin-stimulating agent (ESA) hyporesponsiveness is commonly observed in patients with anemia secondary to chronic kidney disease (CKD). Because of its complexity, a global consensus on how we should define ESA hyporesponsiveness remains unavailable. The reported prevalence and demographic information on ESA hyporesponsiveness within the CKD population are variable with no consensus definition. Summary: ESA hyporesponsiveness is defined as having no increase in hemoglobin concentration from baseline after the first month of treatment on appropriate weight-based dosing. The important factors associated with ESA hyporesponsiveness include absolute or functional iron deficiency, inflammation, and uremia. Hepcidin has been demonstrated to play an important role in this process. Mineral bone disease secondary to CKD and non-iron malnutrition among other factors are also associated with ESA hyporesponsiveness. There is continued debate toward determining a gold-standard treatment pathway to manage ESA hyporesponsiveness. The development of hypoxia-inducing factor-stabilizers brings new insights and opportunities in the management of ESA hyporesponsiveness. Key Message: Management of ESA hyporesponsiveness involves a comprehensive multidisciplinary team approach to address its risk factors. The progression of basic and clinical research on identifying risk factors and management of ESA hyporesponsiveness brings greater hope on finding solutions to eventually tackling one of the most difficult problems in the topic of anemia in CKD.